“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis, 2022)
This article seeks to identify the commercial efforts of Canadian photographers to manufacture and distribute gelatin dry-plates in the 19th century. Using archival material and published advertisements, several companies including the Stanley Dry Plate Company of Montreal are identified and positioned within the photographic manufacturing landscape in Canada. In doing so, the commercial efforts of Canadian manufacturers are contrasted with the parallel developments in dry-plate manufacturing in the United States and England, further situating Canada’s photographic manufacturing history within a broader context.